The Illegal Gold Mining Network In Beutong Subdistrict: A Criminological Analysis And Islamic Legal Perspective : Jaringan Penambangan Emas Ilegal Di Kecamatan Beutong: Analisis Kriminologi Dan Perspektif Hukum Islam - Syahrul Faddli; Delfi Suganda; Riadush Sholihin (Journal of Indonesian Comparative of Syari'ah Law, 2026)
Illegal gold mining in Beutong District, Nagan Raya Regency, constitutes not only a violation of law and a source of environmental degradation but also an organized socio-economic network sustained by power relations and community economic dependency. Previous studies have largely examined illegal mining from environmental, economic, or criminological perspectives separately, with limited integration of social network analysis, patron–client relations, and Islamic legal perspectives. This study analyzes the structure and persistence of illegal gold mining networks through the lenses of differential association theory, patron–client theory, and the Islamic legal concept of ḥifẓ al-bī’ah. Employing a qualitative socio-legal approach, the research draws on statutory analysis, literature review, media documentation, and semi-structured interviews with Yayasan Apel Green Aceh and communities surrounding the mining area. The findings demonstrate that illegal gold mining operates as an integrated network involving logistics suppliers, mining operators, collectors, and gold traders. The sustainability of this network is driven not only by economic incentives but also by patron–client relationships that reinforce dependency and by social learning processes that normalize illegal practices and weaken law enforcement. From the perspective of Islamic law, these activities violate the principles of ḥifẓ al-bī’ah, maṣlaḥah, and the prohibition of fasād fī al-arḍ due to their destructive environmental impacts and adverse consequences for public welfare. This study contributes an integrative framework that combines criminological theory, power relations, and Islamic legal principles to explain the persistence of illegal gold mining in Aceh.